2013
DOI: 10.1080/09670262.2013.772243
|View full text |Cite
|
Sign up to set email alerts
|

Light is a crucial signal for zoosporogenesis and gametogenesis in some green microalgae

Abstract: Patterns of reproduction were investigated in some microalgal species of Chlorophyceae (Botryosphaerella sudetica, Neochloris aquatica, Neochloris vigensis, Bracteacoccus minor). Under continuous light, the microalgae reproduced asexually producing autospores. However, appropriate manipulation of external conditions led to a change in the reproduction pattern towards production of zoospores or gametes. Production of zoospores and gametes was inhibited by light; motile cells emerged when microalgae were cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…While searching for optimal culture conditions, we obtained autospores in N. aquatica cultures exposed to constant light, as well as in photoperiod conditions, where division cells and differences in size were observed in transitions of constant light to darkness, and photoperiod to darkness, respectively. Detected morphologies are also seen in other Chlorophyceae [43], and as previously described by Přibyl [29], no motile cells were found in dark conditions due to their asexual reproduction by autospores. Many microalga metabolites have been described so far, most of them allelochemicals [13,14], which give them relevant advantages.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…While searching for optimal culture conditions, we obtained autospores in N. aquatica cultures exposed to constant light, as well as in photoperiod conditions, where division cells and differences in size were observed in transitions of constant light to darkness, and photoperiod to darkness, respectively. Detected morphologies are also seen in other Chlorophyceae [43], and as previously described by Přibyl [29], no motile cells were found in dark conditions due to their asexual reproduction by autospores. Many microalga metabolites have been described so far, most of them allelochemicals [13,14], which give them relevant advantages.…”
Section: Discussionsupporting
confidence: 82%
“…As during the isolation of the alga, different morphotypes were detected according to the culture conditions, and the objective was to recreate the shape detected in the field samples. For that, the microalga was incubated under different light conditions and constant temperature according to Přibyl [29]. Briefly, overnight culture (OD 750 0.4) was divided in three equal parts, two of them were grown under continuous light, while the other one was cultivated in photoperiod condition (16:8 h light: dark cycles).…”
Section: Microalga Characterizationmentioning
confidence: 99%
“…Light intensity and spectral quality play a significant role in both sporogenesis and gametogenesis in green algae. Short-wavelength (blue) PAR radiation is favorable for massive formation of flagellated cells, whereas long-wavelength (red) PAR blocks it [ 26 ]. In the macrophyte Bryopsis plumosa (Ulvophyceae), a positive effect of UV-A on motile stages production has been reported [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Light microscopic observations of cells is important part of works with unicellular algae (microalgae) [ 11 , 15 ]. The approaches attempted to study algal life cycle also have been reported [ 24 , 26 , 27 ]. In the macrophytic red algae Mastocarpus stellatus and Chondrus crispus an effect of UV-A and UV-B on germination and carpospores viability, as well as on PSA was shown [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Light is also critical to the pattern of reproduction in some micoralgal species. Continuous light leads to asexual reproduction and production of antospores, while darkness can induce zoosporogenesis or gemetogenesis . A recent study of the model green alga Chlamydomonas (Chlorophyta) found that it could grow heterotrophically in the dark on medium supplemented with acetate, and there is some genetic variation in the survival process.…”
Section: Discussionmentioning
confidence: 99%